1988
DOI: 10.1007/bf00614553
|View full text |Cite
|
Sign up to set email alerts
|

Selective inhibition of drug oxidation after simultaneous administration of two probe drugs, antipyrine and tolbutamide

Abstract: The effects of sulphaphenazole, cimetidine and primaquine on the disposition of antipyrine and tolbutamide in healthy volunteers have been investigated. The model substrates were administered simultaneously in order more clearly to define any selective effects of the potential inhibitors. Sulphaphenazole produced a significant increase in the half-life of tolbutamide (7.10 to 21.50 h) and a corresponding decrease in its clearance (0.260 to 0.084 ml.min-1.kg-1). Clearance to hydroxytolbutamide (OHTOL) and carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 43 publications
4
23
0
Order By: Relevance
“…A relative order of modulatory potency is established ( Table 1). The increase in reduction of NNK is similar to that with other chemicals found for inhibition of oxidation of NNK and thereby reduce the NNK-induced tumorigenicity (Back et al, 1988;Hanrahan & Gordon, 1984;Hecht et al, 1990;Inaba et al, 1988;Ioannides et al, 1989;Wright et al, 1991). In addition, the results showed that the amount of NNAL formation was significantly increased with the concentration of microsomal proteins.…”
Section: Correlation Between Nnal Formation and The Vitamin Concentrasupporting
confidence: 65%
“…A relative order of modulatory potency is established ( Table 1). The increase in reduction of NNK is similar to that with other chemicals found for inhibition of oxidation of NNK and thereby reduce the NNK-induced tumorigenicity (Back et al, 1988;Hanrahan & Gordon, 1984;Hecht et al, 1990;Inaba et al, 1988;Ioannides et al, 1989;Wright et al, 1991). In addition, the results showed that the amount of NNAL formation was significantly increased with the concentration of microsomal proteins.…”
Section: Correlation Between Nnal Formation and The Vitamin Concentrasupporting
confidence: 65%
“…(175)) is a weak inhibitor of CYP2C9 in vitro [990], with an apparent K i of 327 M. Coadministration of cimetidine 1 g/day had no effect on the kinetics of tolbutamide but a higher dose (1.6 g/day) decreased the systemic and metabolic clearances of tolbutamide by about 40% in healthy volunteers [1358]. Cimetidine caused only a modest reduction in the clearance of phenytoin, although clinically significant increases in plasma phenytoin levels have been observed in patients receiving long-term phenytoin treatment [1359].…”
Section: Cimetidinementioning
confidence: 99%
“…No effect No ADRAC (1982); Chellingsworth et al (1988); Ellis et at (1984); Kirch et al (1981); Mutschler et at (1984) able and possibly dependent on the dosage of cimetidine studied. When cimetidine was administered at dosages of 1200 and 1600 mgjday, tolbutamide half-life and AUC increased and clearance decreased (Back et al 1988;Cate et al 1986). However, at lower doses of 800 and 1000 mgjday, cimetidine had no significant effect on tolbutamide pharmacokinetics (Back et al 1988;Dey et al 1983;Stockley et al 1986).…”
Section: Other Agentsmentioning
confidence: 90%
“…When cimetidine was administered at dosages of 1200 and 1600 mgjday, tolbutamide half-life and AUC increased and clearance decreased (Back et al 1988;Cate et al 1986). However, at lower doses of 800 and 1000 mgjday, cimetidine had no significant effect on tolbutamide pharmacokinetics (Back et al 1988;Dey et al 1983;Stockley et al 1986). In contrast, Adebayo & Coker (1988) reported that cimetidine 1200 mgjday had no effect on tolbutamide disposition.…”
Section: Other Agentsmentioning
confidence: 90%
See 1 more Smart Citation